Analytical model of stress concentration for the welded joints with angular distortion of thin-walled pipelines. (December 2015) - Adamkowski, Adam; Lewandowski, Mariusz
Abstract: The paper concerns the analysis of stress distribution in the area of welded joints with angular distortion that may appear on the large welded pipelines or vessels. Authors present theoretical considerations leading to a simplified model which allows estimating stress concentrations occurring in this type of irregularities. Derived analytical formulas, fitting for stress calculation in both concave and convex angular distortions, provide an effective engineering tool that requires only a few geometrical parameters describing analyzed defects. This solution allows for quick estimation of the maximal stress concentration factor, which is a measure of the risk level posed by the defect in the thin-walled structures (pipelines, vessels). The correctness of the proposed solution is confirmed by the satisfactory agreement between the results of calculations and the results of strain gauge tests carried out for both types of analyzed imperfections, inventoried on two different hydropower penstocks. Highlights: Large scale thin walled structures with angular distortions at welded joints are considered. Main parameters having impact on SCF in concave/convex angular distortions are defined. Analytical formulas for estimating SCF in the analyzed types of angular distortions are presented. Proposed analytical model are verified basing on field research in Polish hydropower plants.